Cultivation of Berseem (Trifolium alexandrinum) and Oats (Avena sativa) Fodder Crops by Using Biofertilizers and Biopesticide: An Experience from Farmers’ Field in Nadia District of West Bengal - Mohammad, Asif; Chatterjee, Anupam (International Journal of Bio-resource and Stress Management, 2021)
Indiscriminate and unscientific application of chemical fertilizers and pesticides, adversely affect the agricultural production system by damaging soil health, contaminating natural water bodies and ground water. As a result of prolonged use of excessive chemical fertilizers and pesticides, the yield of field crops are decreasing due to poor soil health and produced crops also adversely impact human health. For animal husbandry enterprise, fodder production is one of the major activities. Injudicious use of chemicals can reduce fodder production as well as productivity of livestock can also be reduced. Under these circumstances, demonstration of fodder berseem and oats cultivation by using biofertilizers and biopesticides were carried out in farmer’s field at three blocks of Nadia district of West Bengal, India. The study was conducted in the winter season of the year 2020-21; the selected farmers were trained and method demonstrations of fodder crop production were carried out. The demonstration results suggested that average yield of berseem fodder crop was 53.33±2.80 t ha-1 whereas oats fodder crop was 43.07±2.16 t ha-1. The BC ratio of fodder crop cultivation suggested that, by the cultivation of both fodder crops farmers got substantial economic return. Fodder produced by the using biofertilizers and biopesticide contain good amount of dry matter as well as crude protein. From the study it can be concluded that both the fodder crops can be grown in the farmers’ field of the study area by using the biofertilizers and biopesticide without deteriorating the fodder yield and fodder quality.